ANALISIS UNSUR INTRINSIK PADA CERPEN PUCAT PASI KARYA SALMAA IHSANIA - Aziz Iqbal Firmansyah (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study discusses the analysis of pale short stories by Salma Ihsania with an intrinsic element approach. One of the literary works that tells a lot about personal life or a fairy tale is a short story. One of the analyzes that can be carried out on a literary work is the intrinsic element approach. The intrinsic elements in a short story are theme, characterization, plot, background, point of view, mandate. The purpose of this study was to determine the intrinsic element analysis in a pale short story. Qualitative descriptive method is used to analyze this short story. Reading, analyzing, and marking fragments are ways to get to a text. This method is done so that the intrinsic elements and the value of life in the short story are easily identified, easily understood, and understood by the reader. From this research, the results show that this pale short story by Salma Ihsania contains intrinsic measures including themes, characterizations, points of view, mandate, and settings so it is interesting to read by all groups, both adults and adolescents. After getting the results of this research, it is hoped that the reader will get the intrinsic elements conveyed by the author. Keywords: Analysis, Intrinsic element approach, Pale Pasi Short Story